Calibration, Validation and Performance Evaluation of Swat Model for Sediment Yield Modelling in Megech Reservoir Catchment, Ethiopia - Assfaw, Abebe Tarko (Journal of Environmental Geography, 2019)
Intensive agricultural practice in Ethiopian highlands results in increasing rates of soil erosion and reservoir sedimentation. The estimation of sediment yield and prediction of the spatial distribution of soil erosion on the upper Megech reservoir catchment enables the local governments and policymakers to maximize the design span life of the Megech reservoir through implementing appropriate soil conservation practices. For this study, the sediment yield was estimated and analyzed through hydrological modeling (SWAT). The simulated outputs of the model show that the mean annual surface runoff was 282 mm and the mean annual streamflow was 153 m3/s. Similarly, 12.33 t/ha mean annual total sediment load gets into the Megech reservoir. The model performance standard used to evaluate the model result indicates that the model was superior in performing the trend of runoff and sediment yield in both calibration and validation periods. Finally, the most erosion vulnerable sub-basins that could have a significant impact on the sediment yield of the reservoir were identified. Based on this, sub-basin 7, 25, 27, 18 and 29 were found to be the most erosion sensitive areas that could have a significant contribution to the increment of sediment yield in the Megech reservoir. Considering the land use, soil type, slope, and relief of erosion vulnerable sub-basins cut off drains, fallow land, contour ploughing, Fanya juu terraces, soil bunds combined with trenches and trees could be the possible management strategies to reduce the sediment yield in the catchment.